A climate‐compatible approach to development practice by international humanitarian NGOs. Issue 1 (January 2015) - Clarke, Matthew; de Cruz, Ian
<x xml:space="preserve">Abstract</x> If current climate‐change predictions prove accurate, non‐linear change, including potentially catastrophic change, is possible and the environments in which international humanitarian NGOs operate will change figuratively and literally. This paper proposes that a new approach to development is required that takes changing climate into account. This 'climate‐compatible approach' to development is a bleak shift from some of the current orthodox positions and will be a major challenge to international humanitarian NGOs working with the most vulnerable. However, it is necessary to address the challenges and context such NGOs face, and the need to be resilient and adaptive to these changes.